Jason S. answered • 11/12/13

Tutor

4.9
(116)
My goal is the success of my students. Knowledge-Patience-Honesty

(3x + 6) (3x - 6)

(x-8) (x-3)

I don't understand the second part of your question.

Jason S.

Nataliya D. was correct on the first one. I didn't factor out the 9 first.

The correct answer was 9(x-2) (x+2).

The correct answer was 9(x-2) (x+2).

9x^2-36 = (3x+6) (3x-6) = 3(x+2)(3)(x-2) = 9(x-2)(x+2)

Or the best way 9(x^2-4) = 9(x-2)(x+2).

My apologies that in my haste I didn't COMPLETELY factor the expression.

Or the best way 9(x^2-4) = 9(x-2)(x+2).

My apologies that in my haste I didn't COMPLETELY factor the expression.

Report

11/13/13

Samuel W.

11/12/13